Padrões de coloração do tucunaré azul (Cichla piquiti) noreservatório de Lajeado, Rio Tocantins, TO - Borges, Lucas Elias Oliveira (Universidade Federal do Tocantins, 2024)
The blue peacock bass, Cichla piquiti and the yellow peacock bass, Cichla kelberi areendemic species of the Tocantins River basin. They are found in different environments of theLajeado HPP reservoir and show color variation between equals of the same species. The present work aims to describe variations in the color pattern of the blue peacock bass, C. piquiti, in the Lajeado reservoir, rio Tocantins, and to investigate biological and environmental factors that may determine variation in the pattern. The collections of biological material were carried out from August 2019 to August 2020, in the city of Porto Nacional -TO, always during the day (8am - 6pm), in 12 sampling points distributed over an approximate length of 15 km. In the field, each individual's colors were recorded to determine color patterns. Two shades were considered for the body (blue and brown) andthree for the fins (blue, brown and red). 87 individuals of C. piquiti were analyzed. The difference in the proportion of blue and brown individuals in the population is noticeable,with a predominance of brown coloration. Patterns observed in the body, caudal and dorsal fins, revealed that the blue color predominates in individuals in reproductive activity, and that they have a larger body size. The environmental variables do not seem to influence the color pattern of C. piquiti. The data showed that coloration is not related to sexual dysmorphism of the species, but to gonadal growth and development. The data also showed that the presence of blemishes on the body is associated with young individuals, but they are common in thefins of most fish.